-2(3t-2)+3t=6t-3

Simple and best practice solution for -2(3t-2)+3t=6t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3t-2)+3t=6t-3 equation:


Simplifying
-2(3t + -2) + 3t = 6t + -3

Reorder the terms:
-2(-2 + 3t) + 3t = 6t + -3
(-2 * -2 + 3t * -2) + 3t = 6t + -3
(4 + -6t) + 3t = 6t + -3

Combine like terms: -6t + 3t = -3t
4 + -3t = 6t + -3

Reorder the terms:
4 + -3t = -3 + 6t

Solving
4 + -3t = -3 + 6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-6t' to each side of the equation.
4 + -3t + -6t = -3 + 6t + -6t

Combine like terms: -3t + -6t = -9t
4 + -9t = -3 + 6t + -6t

Combine like terms: 6t + -6t = 0
4 + -9t = -3 + 0
4 + -9t = -3

Add '-4' to each side of the equation.
4 + -4 + -9t = -3 + -4

Combine like terms: 4 + -4 = 0
0 + -9t = -3 + -4
-9t = -3 + -4

Combine like terms: -3 + -4 = -7
-9t = -7

Divide each side by '-9'.
t = 0.7777777778

Simplifying
t = 0.7777777778

See similar equations:

| 2(x+4x)=5x-8 | | 0=y+2/3 | | -7x-y=17 | | 2x(x+4)=5x-8 | | .5-1.1=4.0 | | s(t)=-16t^2+68t+20 | | 4x^3-7x^2-15x=0 | | 6x+1+5x=133 | | 1/4x+12=1/2x+10 | | 3p-1=5(-4x+4) | | 8z-z=-2+3z-3-7 | | y+1=-9(x+5) | | 65+x+(x-5)=1 | | H^2+5h-21=0 | | 6-3z+8=8-4z | | y=1.4+0.8x-0.01x^2 | | 7(x+9)=21 | | -10=2x-10 | | -10+4x-6=12 | | A(x)=x(16-2x) | | 3x-.3(6-x)=3.9 | | (-0.75x-8)-(1.5x+8.4)= | | -16=8(x+3) | | -5(1-5x)+5(-8x-2)= | | 2n-3(4n+5)=-6n+17 | | s+87.8=3.81 | | 8x-15=5x-34 | | 10log=30 | | 1.15+.8x=2.3-1.5 | | 3y+6x=1 | | 1x/4x+3=3x/4x-7 | | 2x+12=4x-5 |

Equations solver categories